Comparison of Moderate and High Energy of a Nano-Fractional Radiofrequency Treatment on a Photoaging Hairless Mice Model. Issue 4 (April 2018) - Sun, Wenjia; Zhang, Chengfeng; Zhao, Juemin; Wu, Jiaqiang; Xiang, Leihong
Abstract : BACKGROUND: Fractional radiofrequency (FRF) has been widely used in skin rejuvenation. To explore optimal settings, it is important to compare different treatment parameters. OBJECTIVE: This study was designed to compare the effect of moderate-energy and high-energy FRF treatment on a hairless mice model. METHODS: Fifteen photoaged hairless mice were assigned to 3 groups: control, moderate energy, and high energy. Two treatment sessions (T × 1 and T × 2) were performed at 1-month interval. Transepidermal water loss was measured at baseline, immediately, 1, 2, and 4 weeks after T × 1. Skin samples were harvested before each treatment, 1 and 2 months after T × 2. Neocollagenesis was evaluated by hematoxylin and eosin staining, Masson staining, and immunohistochemistry analysis. RESULTS: Transepidermal water loss of high-energy group was significantly higher than the moderate-energy group ( p = .008) immediately after T × 1. Remarkable fibroblast proliferation was observed at 1 month after T × 1, followed by significant dermal thickening, and increase of Type I collagen and Type III collagen. There was no significant difference between 2 energy groups in fibroblast proliferation, dermal thickness, and collagen density. CONCLUSION: The effect of moderate-energy treatment was comparable with that of high energy in neocollagenesis, whereas moderate energy yielded less damage to skin barrier function.